Prospects and challenges of issuance of Sukuk in Bangladesh: Lessons from Malaysia for developing a comprehensive legal framework for Bangladesh - Hasan, AKM Raquibul (Dhaka University Law Journal, 2022)
The introduction of Islamic Bond Sukuk in Bangladesh has created a new source of funding for the government and private sector. Favourable legal framework is necessary for the growth of Sukuk in Bangladesh. The core objective of this paper is to examine the domestic legal framework of Sukuk and to find out its compatibility with international standards, more particularly with the Malaysian regime. This paper offers a brief discussion on the prospects of Sukuk in Bangladesh and then outlines the challenges and limitations of Sukuk market. Part five of this article investigates the loopholes in the existing regulations in Bangladesh. Finally, this paper argues that while Bangladesh has established a regulatory guideline for prudential management of Sukuk, there is still room for improvement for efficient operation and effective management of Sukuk. Notably, this paper explores the Malaysian legal regime to find out the critical areas of reform in Sukuk regulations in Bangladesh. Dhaka University Law Journal, 2022, 33(1), 163-184